Patchoili oil extraction using ultrasonic extraction method - Mohd Nashriq, Nasharudin (2008)
Essential oil is an aromatic liquid that is extracted from various parts of the plants. It contains the true essence of the plant. Patchouli essential oil is primarily used in the perfumery industry and has a very high commercial value due to its therapeutic properties. Recently, this essential oil has high demand all over the world due to its usages in the daily life. In this research, Patchouli oil is extracted from dried Patchouli (Pogestemon Cablin) leaves. The purpose of this research is to determine the best condition in order to get higher yield of patchouli oil using the ultrasonic wave. The method used in this research to extract this patchouli oil is ultrasonic extraction method. The ultrasound is used to penetrate into the leave cells to extract the patchouli essential oil from the leaves. Water is used as the extraction medium in this process. Basically, there are two parameters have been studied which are extraction temperature and extraction time. In the first experiment, the extraction time is varies into four different times which are 1.5, 2.0, 2.5 and 3.0 hours. For the second experiment, the extraction temperature is varies into four different temperatures which are 50°C, 65°C, 80°C and 95°C. Based on these parameters, the best condition to obtain the best oil yield is determined at three hours extraction time and 95°C extraction temperature.